PERSEPSI MAHASISWA TERHADAP STRATEGI PILIHAN BAHASA DOSEN DI KELAS - Savitri, Eka Dian (Jurnal Pena Indonesia, 2019)
The language choice strategy of the lecturer has implications for the success of the communication process in the classroom. This can be known through student perception. This study aims to prove this relationship by (1) describing the use of local languages, national languages, and foreign languages by lecturers in regular classes (nonbilingual class); (2) describe student perception of the classroom atmosphere developed; and (3) describe students’ perceptions of the lecturer’s character. This study used qualitative research with case study design. The selected research participants were 11 teaching assistants at Sepuluh Nopember Institute of Technology. Data were collected using interview techniques and produced a description of the use of language in the classroom by 33 lecturers. The data is classified based on the dimensions of positive words and negative words as well as the dimensions of competence and social attractiveness. The research concluded that (1) most of the lecturers used their multilingual skills in the classroom; (2) the more variety of languages used by lecturers shows the perception of a conducive and attractive classroom atmosphere; (3) the more variety of languages used by lecturers shows the higher dimensions of competence and social attractiveness. The results of this study can be a reference to language choices strategies for lecturers to create effective communication in the learning process in class.Akynova, D. et al. (2014) ‘Language Choice Among the Youth of Kazakhstan: English as a Self-Representation of Prestige’, Procedia - Social and Behavioral Sciences. Elsevier B.V., 143, pp. 228–232. doi: 10.1016/j.sbspro.2014.07.393.Bogunovi, I. (2017) ‘Language & Communication Person perception and language : A case of English words in Croatian’, Language & Communication journal, 53, pp. 25–34. doi: 10.1016/j.langcom.2016.11.001.Dragojevic, M., Berglund, C. and Blauvelt, T. K. (2014) ‘Attitudes Toward Tbilisi- and Mingrelian-Accented Georgian Among Georgian Youth: On the Road to Linguistic Homogenization?’, Journal of Language and Social Psychology. SAGE Publications Inc, 34(1), pp. 90–101. doi: 10.1177/0261927X14555191.Genesee, F. and Bourhis, R. Y. (1988) ‘Evaluative reactions to language choice strategies: The role of sociostructural factors’, Language and Communication, 8(3–4), pp. 229–250. doi: 10.1016/0271-5309(88)90020-1.Henderson, K. I. (2017) ‘Teacher language ideologies mediating classroom-level language policy in the implementation of dual language bilingual education’, Linguistics and Education. Elsevier Inc., 42, pp. 21–33. doi: 10.1016/j.linged.2017.08.003.Heredia, R. R. and Altarriba, J. (2001) ‘Bilingual Language Mixing: Why Do Bilinguals Code-Switch?’, Current Directions in Psychological Science. SAGE Publications Inc, 10(5), pp. 164–168. doi: 10.1111/1467-8721.00140.Jiang, Y. L. B., García, G. E. and Willis, A. I. (2014) ‘Code-Mixing as a Bilingual Instructional Strategy’, Bilingual Research Journal, 37(3), pp. 311–326. doi: 10.1080/15235882.2014.963738.Schwartz, M. and Asli, A. (2014) ‘Bilingual teachers ’ language strategies : The case of an Arabic e Hebrew kindergarten in Israel’, Teaching and Teacher Education. Elsevier Ltd, 38, pp. 22–32. doi: 10.1016/j.tate.2013.10.013.Thomas M. Holtgraves and Yoshihisa Kashima (2007) ‘Language, Meaning, and Social Cognition’, Personality and Social Psychology Review, 12(1), pp. 73–94. doi: https://doi.org/10.1177/1088868307309605.Tian, L. and Hennebry, M. (2016) ‘Chinese learners’ perceptions towards teachers’ language use in lexical explanations: A comparison between Chinese-only and English-only instructions’, System. Elsevier Ltd, 63, pp. 77–88. doi: 10.1016/j.system.2016.08.005.